Mentorship in the Field of Aging: Purposes, Pivots, and Priorities - Patricia W. Slattum; Tiffany R. Washington; Sarah Dys; Patricia M. D'Antonio; Tonya J. Roberts; Matthew Lee Smith (New Prairie Press, 2022)
The Gerontological Society of America (GSA) is a multi-disciplinary organization dedicated to advancing the field of aging and improving the lives of older adults. With a long-standing commitment to mentorship and career development, this article focuses on GSA's Mentoring Consultancies and Career Conversations events and their pivot to meet the needs and demands of current and future gerontologists amid the COVID-19 pandemic. This article provides a description of these events in the context of planning, content, and member engagement. Recommendations are provided to other organizations seeking to enrich their membership through mentorship and career development activities.